Neonatal Hyperbilirubinemia Due to AB0 Incompatibility - Takci, Sahin; Anuk Ince, Deniz; Hendekci, Ayse; Eren, Nagehan (Annals of Medical Research, 2021)
Aim: ABO incompatibility is a common condition occurring in about 15-25% of all maternal/fetal pairs. The features of ABO incompatibility range from asymptomatic through to severe hemolysis with hyperbilirubinemia and anemia. The aim of this study is to assess the clinical course of ABO incompatibility and to evaluate the effect of blood groups on the severity of neonatal jaundice.
Keywords: Neonate; Jaundice; ABO Incompatibility; Blood Group; Phototherapy.